Capturing the diversity of the human milk microbiota through culture-enriched molecular profiling: a feasibility study. Issue 3 (8th January 2021) - Moossavi, Shirin; Fontes, Michelle E; Rossi, Laura; Fusch, Gerhard; Surette, Michael G; Azad, Meghan B
ABSTRACT: Previous human milk studies have confirmed the existence of a highly diverse bacterial community using culture-independent and targeted culture-dependent techniques. However, culture-enriched molecular profiling of milk microbiota has not been done. Additionally, the impact of storage conditions and milk fractionation on microbiota composition is not understood. In this feasibility study, we optimized and applied culture-enriched molecular profiling to study culturable milk microbiota in eight milk samples collected from mothers of infants admitted to a neonatal intensive care unit. Fresh samples were immediately plated or stored at −80°C for 2 weeks (short-term frozen). Long-term samples were stored at −20°C for >6 months. Samples were cultured using 10 different culture media and incubated both aerobically and anaerobically. We successfully isolated major milk bacteria, including Streptococcus, Staphylococcus and Bifidobacterium, from fresh milk samples, but were unable to culture any bacteria from the long-term frozen samples. Short-term freezing shifted the composition of viable milk bacteria from the original composition in fresh samples. Nevertheless, the inter-individual variability of milk microbiota composition was observed even after short-term storage. There was no major difference in the overall milk microbiota composition between milk fractions in this feasibility study. This is among the first studies on culture-enriched molecular profiling of the milk microbiota demonstrating the effect of storage and fractionation on milk microbiota composition. Abstract : Culture-enriched molecular profiling of milk microbiota and the effect of storage and milk fractions.